The role of estrogen receptor (ER) signaling in mitigating radiation-induced cardiotoxicity (RIC) in mouse models subjected to total body irradiation - Adhikari, Sam, author; Chicco, Adam, advisor; Olivo-Delgado, Carlos, committee member (Colorado State University. Libraries, 2026)
Radiation can be a significant concern for cancer survivors and radiation exposed to victims. Within the proposal document from Dr. Adam Chicco's lab, (Milestone 3) highlights a significant discrepancy in cardiac mortality rates between atomic bomb survivors and childhood cancer survivors. This difference likely stems from the nature of the exposure to total body irradiation (TBI) versus organ-specific (partial) radiation. A critical factor in TBI is the extreme radiosensitivity of the ovaries. Because the ovaries have a limited, non-renewable pool of oocytes (eggs), even low doses of radiation can cause premature ovarian failure (Adriaens et al.). This study investigates whether estrogen replacement can mitigate these effects when radiation is induced. Using a mouse model, estradiol capsules are used to maintain physiological estrogen levels following radiation exposure. Radiation exposure promotes cardiac scarring and stiffness, weakening the heart muscle's ability to pump blood effectively. To analyze these effects, echocardiography is utilized to visualize the anatomy of the heart. Consistent with the previous findings, estrogen replacement can help minimize pathological cardiac remodeling (Szabó et al.). While this research encompasses multiple analytical approaches, this paper focuses specifically on echocardiographic observations to understand the effects of RIC.
Keywords: cardiotoxicity; estrogen; radiation; total body irradiation; estradiol